Complete Silage of Forage Corn and King Grass on Weight Gain and Physiological Status of Goat and Sheep - Nirwana, Nirwana; Wulan, Sri; Zainal, Zainal (AgriSains, 2021)
This research was conducted in the experimental cage owned by CV. Prima BREED in Tondo Village, Mantikulore Subdistrict, Palu City, Central Sulawesi Province from March to June 2017. This research aims to find out the weight gain of dry matter consumption, the efficiency of dry matter use, body temperature, respiration frequency, and pusus frequency of Kacang goat and sheep which are given complete silage made from corn and king grass. The number of livestock used in this research was 12 female goats and 12 sheep aged Â±Â  10 months. The environmental design used in this research was a 2 x 2 factorial pattern Completely Randomized Design (CRD) and repeated 6 times. The first factor is the type of livestock (goats and sheep). The second factor consists of two types of complete silage, namely P1 = complete silage made from forage corn and P2 = complete silage made from king grass. The results of the analysis of variance show that there is an interaction between types of livestock and complete silage on the consumption of dry matter, but there is no significant effect on body weight gain, efficiency in the use of dry matter rations, body temperature, respiration frequency and frequency of pulses. Goats have a significantly higher body weight gain, but body temperature and pulsus frequency are lower than sheep, however dry matter consumption, ration efficiency, and frequency of respiration do not show any significant differences. Complete silage do not show any significant differences in body weight gain, dry matter consumption of rations, the efficiency of use of dry matter of rations, body temperature, frequency of respiration, and frequency of pulses.